Lectotypification of Gastrodia dyeriana King & Pantl. (Orchidaceae), its threat status assessment as per IUCN guidelines and notes on its first authentic voucher specimen from Arunachal Pradesh, India - Chakraborty, Sayak; Sengupta, Sanchayita; Chakraborty, Oindrila; Agrawala, Dinesh Kumar; Bhattacharjee, Avishek; Maity, Debabrata (Phytotaxa, 2025)
Gastrodia dyeriana King & Pantling [Orchidaceae-Epidendroideae-Gastrodieae], earlier known as an endemic species in India, was first reported from Sikkim. As part of the ongoing revisionary work on the genus Gastrodia Brown, it has been found that the name G. dyeriana is not typified. Therefore, a lectotype has been selected for the name. Moreover, the species was reported from Arunachal Pradesh earlier, which lacked citation of any authentic voucher specimen. During a recent field survey in Arunachal Pradesh, the species was collected from a different location. A detailed description along with photographic illustration, data on phenology, habitat and updated distribution is provided for easy identification. Conservation status of the species has also been assessed during the present study following the IUCN guidelines.